ETD: Educação Temática Digital Vol. 13, n. 1 (2011) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2012)
Acesso ao númerohttp://www.fae.unicamp.br/revista/index.php/etd/issue/view/162/showToc